Ritual and Mythology of the Chinese Triads: Creating an Identity - Haar, Barend J. ter (Brill Book Archive Part 1, ISBN: 9789004472495, 2000)
The extensive ritual and mythological lore of the Chinese Triads form the scope of this new paperback title in Brill's Scholars' List. The author critically evaluates the extant sources and offers a wealth of contextual information. The core of the book is formed by a close reading of the initiation ritual, including the burning of incense, the altar, the enactment of a journey of life and death, and the blood covenant. Different narrative structures are also presented. These include the messianic demonological paradigm, political legitimation, and the foundation of myth. Triad lore is placed in its own religious and cultural context, allowing radically new conclusions about its origins, meanings and functions. This book is of special interest to social historians, anthropologists, and students of Chinese religious culture